2013
DOI: 10.1007/s11032-013-9885-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of transposable element mPing as a novel genetic tool for modification of the stress response in rice

Abstract: Transposable elements (TEs) are DNA fragments that have the ability to move from one chromosomal location to another. The insertion of TEs into gene-rich regions often affects changes in the expression of neighboring genes. Miniature Ping (mPing) is an active miniature inverted-repeat TE discovered in the rice genome. It has been found to show exceptionally active transposition in a few japonica rice varieties, including Gimbozu, where mPing insertion rendered adjacent genes stress-inducible. In the Gimbozu po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…Tissue culture has been shown to result in activation of transposons and retrotransposons in a number of plant species [30]- [31]. There are also examples of transcriptional activation of TEs in response to specific abiotic stresses in tobacco [22], rice [26]- [27] and Arabidopsis [16], [28]- [29]. It is expected that the stress The relative expression levels in stress compared to control treatments (log 2 ratio) is shown for B73, Mo17, and Oh43 for each of the 10 expressed genes that are polymorphic for insertions of TEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue culture has been shown to result in activation of transposons and retrotransposons in a number of plant species [30]- [31]. There are also examples of transcriptional activation of TEs in response to specific abiotic stresses in tobacco [22], rice [26]- [27] and Arabidopsis [16], [28]- [29]. It is expected that the stress The relative expression levels in stress compared to control treatments (log 2 ratio) is shown for B73, Mo17, and Oh43 for each of the 10 expressed genes that are polymorphic for insertions of TEs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of the tobacco Tnt1 element can be induced by biotic and abiotic stress [22]- [23]. The rice DNA transposon mPing can be activated in response to cold and salt stress [26]- [27]. The Arabidopsis retrotransposon ONSEN is transcriptionally activated by heat stress [16], [28]- [29].…”
Section: Introductionmentioning
confidence: 99%
“…These are experimental evidences that TEs have the capacity to alter regulatory networks at posttranscriptional level. Our previous studies showed that the rice active MITE mPing renders adjacent genes stress inducible when it is inserted within 0.5-kb upstream of the transcription start site (Naito et al 2009;Yasuda et al 2013). In this study, we found that mPing induces alternative splicing and alternative polyadenylation when it is inserted within the coding sequence of genes.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, it was found that, in EG4, mPing is mobilized in the embryo with the aid of the developmental stage-specific up-regulation of its autonomous element, Ping (Teramoto et al 2014). mPing preferentially transposes into within 0.5-kb upstream of gene and renders adjacent genes stress inducible (Naito et al 2009;Yasuda et al 2013), which indicates that, like other MITEs, mPing also contributes to the generation of new regulatory networks at the transcriptional level. Little is known, however, about the effects of mPing on the posttranscriptional regulation of genes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in rice, the mPing , a miniature inverted-repeat transposable elements (MITE) family, rapidly expanded in specific strains and its insertions into the 5’ flanking region rendered adjacent genes inducible by abiotic stresses by introducing cis -regulatory elements and/or epigenetic markers (Naito et al, 2009; Yang et al, 2005; Yasuda et al, 2013). Similarly, we observed that insertions of the DTT-NIC1, a Solanaceae specific MITEs family that contains a stress inducible cis -regulatory element, the W-box, into 5’ regulatory regions of genes are significantly enriched among genes of the HAE-induced EDS network in Nicotiana ( p=0.00049, Appendix 1).…”
Section: Discussionmentioning
confidence: 99%